The Optimization of Building Integrated Photovoltaic (BIPV) Roof in Residential Buildings in Yogyakarta - Arsyad Amirul Azmi; Alexander Rani Suryandono (Universitas Muhammadiyah Surakarta, 2026)
Solar panel technology is expected to mitigate the impact of global warming with the use of Building Integrated Photovoltaic (BIPV) that incorporates solar panels into buildings. However, the application of BIPV still has limitations in architectural design, especially for housing in Yogyakarta. This study uses a quantitative approach with a design-based simulation method through exploration of the best roof shape for BIPV type-72 houses in Yogyakarta. This study aims to identify the most optimal roof shape of type-72 houses in utilizing solar energy potential through the application of the BIPV system in residential areas in Yogyakarta. Through a quantitative design-based simulation approach, 72 combinations of roof models integrated with variations in orientation, plot shape, and floor plan shape are analyzed to measure the estimated annual energy production per installed PV area (kWh/m²/year). On average, the gable roof shape has the highest value in the application of BIPV on the roof for each orientation scenario, plot shape and floor plan shape. While the most optimal design per scenario is a sloping roof shape facing north, a 10m x 12m plot shape, and a single building mass floor plan with a garden in the middle. The optimal condition is obtained by combining all scenarios which gives 10.4% better performance compared to the average of all simulation results.